Efficiency Analysis of Bank Buku 4 (Bank with Core Capital at Least Rp30 Trillion) Before and During The Covid-19 Pandemic: Efficiency Analysis of Bank Buku 4 (Bank with Core Capital at Least Rp30 Trillion) Before and During The Covid-19 Pandemic - Budi Santosa; Nurhayati; Nur Hidayatullah (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2023)
The purpose of the study is to analyze Bank BUKU 4 Financial performance the COVID-19 Pandemic, until the years of the pandemic. The research based on secondary data, sourced from annual and finansial reports of banks in Bank BUKU 4 category along with source from www.ojk.com. Every banking companies in Indonesia are the population for this reseach. While the sample of this research are ten (10) banks that categorized as Bank BUKU 4 from 2018 until 2010 with purposive sampling technique. Data Envelopment Analysis (DEA) on non-parametric term testing used the intermediation approach become efficiency measurement method in this study. Total Assets, Deposits, Total Savings, and Operating Costs are the input variables. While the output variables contained in this study are Credit, Interest Income, and Net Income. There are two results based on this study; First, most of banks that included as Bank BUKU 4 measured to have high efficiency, although Bank Permata and CIMB have reached the level moderate in efficiency in some years. Second, the banks’ efficiency in Bank BUKU 4 category has No. difference on the study period